Formulasi Minuman Fungsional Dawet Kaya Protein Berbasis Kacang Hijau dengan Suplementasi Limbah Ampas Tahu (Okara) - Netta Meridianti Putri; Resti Kurnia Triastanti; Mira Dian Naufalina (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The development of a mung bean-based dawet functional drink with supplementation of tofu waste (okara), is an alternative for providing protein-rich functional drinks based on local potential. By considering various potentials and advantages, such as high nutritional content, use of local ingredients, natural composition, absence of use of preservatives, relatively cheap production costs, and easy availability of ingredients, the innovation of mung bean-based dawet functional drinks with the addition of okara flour is promising as a an interesting product to develop further. The aim of the research was to determine the effect of tofu waste (okara) flour supplementation in mung bean-based dawet functional drinks on sensory characteristics. This research used a Randomized Block Design (RAK) with the addition of tofu waste flour, P1 = 10%, P2 = 15%, P3 = 20%, and substitution of mung bean flour with the proportion of rice flour : mung bean flour P1 = 70% : 30% , P2 = 50% : 50%, P3 = 30% : 70%. The most preferred Dawet variant has a special composition, consisting of 30% tofu waste flour, 50% rice flour and 50% mung bean flour. The panelists gave the highest marks to this variant, indicating that the combination of ingredient proportions provided the most satisfying and desirable sensory experience in terms of texture, taste, color and aroma.